2009
DOI: 10.1116/1.3106626
|View full text |Cite
|
Sign up to set email alerts
|

Gas temperature measurement in CF4, SF6, O2, Cl2, and HBr inductively coupled plasmas

Abstract: Neutral gas temperature (Tg) is measured in an industrial high-density inductively coupled etch reactor operating in CF4, SF6, O2, Cl2, or HBr plasmas. Two laser diodes are used to deduce Tg from the Doppler widths of 772.38 and 811.5nm lines absorbed by Ar*(P23) metastable atoms, when a small amount of argon (5%) is added to the gas flow. With the 811.5nm beam passing parallel to the wafer, Tg near the wafer surface is obtained by laser absorption technique. With the 772.38nm beam entering the top of the reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 34 publications
3
39
0
Order By: Relevance
“…2, because this flux is obtained by integration of the IVDF and less sensible to noise. The measured T i ¼ 0.27 eV is far above the expected neutral temperature (<0.07 eV near the wafer 16 ), but it is in excellent agreement with ion temperatures measured in the high density plasma. 17 From a long set of experiments in various gases and rf power (not shown), we concluded that ions in ICP reactor operated in typical conditions have a temperature of about 2500-3000 K.…”
supporting
confidence: 78%
“…2, because this flux is obtained by integration of the IVDF and less sensible to noise. The measured T i ¼ 0.27 eV is far above the expected neutral temperature (<0.07 eV near the wafer 16 ), but it is in excellent agreement with ion temperatures measured in the high density plasma. 17 From a long set of experiments in various gases and rf power (not shown), we concluded that ions in ICP reactor operated in typical conditions have a temperature of about 2500-3000 K.…”
supporting
confidence: 78%
“…With TDL off, I back ðÞ and I plasma ðÞ are recorded without and with plasma, respectively. So the spectral dependent absorbance 32…”
Section: B Data Treatmentmentioning
confidence: 99%
“…Gas heating is basically reduced due to a lower average source power in pulsed mode. Assuming that H and H 2 have a similar density to Br and Br 2 , respectively, and neglecting O-containing species, we can estimate the plasma temperature around 650 K in CW mode, consistent with the literature [11]. The temperature decreases and is expected to tend towards 330 K at very small duty cycle.…”
Section: Plasma Diagnostic Without Silicon Etchingmentioning
confidence: 67%